2012
DOI: 10.1590/s0006-87052012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Producción de tomate tipo italiano en función del volumen de la celda y de la edad de las mudas

Abstract: ResumenCon el objetivo de evaluar la influencia de las bandejas de celdas sobre la producción de tomate tipo italiano en el campo, se realizó este trabajo en Piracicaba, SP, Brasil, de mayo a agosto del 2005. Los tratamientos consistieron en cuatro volúmenes de recipiente, tres bandejas de poliestireno expandido de 121,2; 34,6 y 12,0 cm³ y de una bandeja de plástico rígido de 14,0 cm 3 (72, 128, 288 y 450 celdas, respectivamente) combinadas con cuatro edades para el trasplante (19, 24, 29 y 34 días después de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…Seedlings of 14.26 and 16.97 cm height were obtained using volume of substrate of 22 and 100 cm 3 and 30 days in the nursery. These results were similar to the ones obtained by Sánchez et al (2012) (Oviedo et al, 2012;Oagile et al, 2016).…”
Section: Substrate Volumes and Nursery Dayssupporting
confidence: 93%
See 1 more Smart Citation
“…Seedlings of 14.26 and 16.97 cm height were obtained using volume of substrate of 22 and 100 cm 3 and 30 days in the nursery. These results were similar to the ones obtained by Sánchez et al (2012) (Oviedo et al, 2012;Oagile et al, 2016).…”
Section: Substrate Volumes and Nursery Dayssupporting
confidence: 93%
“…This may be because by increasing the volume of the cavity and therefore the substrate, the flowering and harvest earliness are increased (Cooper et al, 2002;Sanchez et al, 2012). In addition, a larger volume of substrate improves the quality of seedlings, because it has better balance between shoot and root system and no stress post-transplant (Seabra et al, 2004;Oviedo et al, 2012).…”
Section: Earliness Of Harvestmentioning
confidence: 99%
“…In addition, greater water retention capacity leads to better aerial growth. In this regard, Oviedo and Minami [2012] reported that the cell size of containers significantly increased the height of tomato transplants. On the other hand, it was reported an increase in the height of the bean plant (Phaseolus vulgaris L.) and wheat (Triticum aestivum L.) with the use of N, which was consistent with our results [Salehin andRahman 2012, Hassanein et al 2018].…”
Section: Discussionmentioning
confidence: 99%
“…A produção em larga escala de mudas tem motivado os produtores a adotar novas técnicas, métodos e equipamentos (OVIEDO et al, 2012). Produtores de mudas de tomate industrial têm enfrentado diversos desafios, aprimorando e buscando novas tecnologias, principalmente no exterior, e realizando suas próprias pesquisas (NASCIMENTO et al, 2013).…”
Section: Introductionunclassified